A novel scheme for weld microstructure control using cryogenic cooling - Amuda, Muhammed Olawale Hakeem; Mridha, Shahjahan (2009)

(untitled)
The total energy input and heat transfer factors influence the after-weld microstructural features and hence properties of the joint. Low heat input has been suggested for fusion welding in order to avoid unfavourable grain morphologies in the welds. Also, the weld cooling cycle is crucial in the control of weld microstructures, particularly the time spend above the critical temperature. This is probably controlled by the heat dissipation mechanism in fusion welds from the peak temperature to the ambient condition. However, the influence of the heat transfer factor in terms of the cooling dynamics on the microstructural features and properties of welds have not been well investigated. Additional cooling can assist in the heat dissipation mechanism and hence it can be extremely beneficial to the control of the post-weld microstructure and helps in minimizing the grain growth. In this work, the preliminary result on the effect of cryogenic cooling on grain growth in weld is reported. Ferritic stainless steel, cooled in liquid nitrogen, is welded under TIG torch in argon environment. The weld structure is characterized using LOM, SEM and EDX spectroscopy. The results suggest that cryogenic cooling reduced the weld width within 2% to 5% and HAZ to 39% relative to those cooled in normal condition. This ensures that the area of the base metal affected and exposed to the weld thermal cycle is reduced and hence probably generates less metallurgical distortion. The cryogenic cooling also generated 14% to 36% grain refinement compared to welds cooled in normal condition.